2006
DOI: 10.1002/app.22169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature on electrical behavior of flyash‐filled epoxy gradient composites

Abstract: Functionally gradient composites of epoxy resin having different weight percentages of flyash were prepared under centrifugal force to obtain gradient in density, hardness, and electrical properties. Effect of temperature and frequency variation on dielectric constant (Ј), tan ␦, and ac conductivity was determined by using a 4274 A Multi-Frequency LCR meter. Electrical measurements were carried out in a temperature range from 40 to 180°C and in a frequency range from 1 to 100 kHz. It was observed that the diel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…When the IPEP contents were lower than 50 wt %, the hardness increased with the IPEP contents. As the inorganic silica segments (POSS) increased and covalent bonds of the inorganic POSS segments formed across the interface between the inorganic segments and organic segments 47–48. Liu et al49 indicated that introduction of the inorganic segments into the polymer materials could improve the wear resistance and surface hardness of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…When the IPEP contents were lower than 50 wt %, the hardness increased with the IPEP contents. As the inorganic silica segments (POSS) increased and covalent bonds of the inorganic POSS segments formed across the interface between the inorganic segments and organic segments 47–48. Liu et al49 indicated that introduction of the inorganic segments into the polymer materials could improve the wear resistance and surface hardness of the nanocomposites.…”
Section: Resultsmentioning
confidence: 99%
“…Fly ash has also been used in the development of functionally graded polymer composites to obtain gradient in density, hardness and electrical properties. 6 It has been advocated that fly ash can be used as filler or the supporting filler in the polymers. 7 The fine fly ash particles improve dielectric properties, rigidity and heat deflection temperature of polymers.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to several commercial fillers such as silica, calcium carbonate, talc, carbon black, rutile, etc., the fly ash has been incorporated in polymers to improve mechanical, thermal, and electrical properties. Fly ash has also been used in the development of functionally graded polymer composites to obtain gradient in density, hardness and electrical properties 6. It has been advocated that fly ash can be used as filler or the supporting filler in the polymers 7.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bose and Mahanwar 5 observed that the addition of fly ash to nylon 6 improved its rigidity, heat resistance, and dimensional stability. Chand et al 6,7 developed a new type of cheaper fly ash-filled PP/polymethyl methacrylate blend system and also studied the effect of temperature on electrical behavior of fly ash-filled epoxy gradient composites. Kishore et al [8][9][10][11] investigated the compressive properties of epoxy and hybrid epoxy composites filled with fly ash under different conditions.…”
Section: Introductionmentioning
confidence: 99%